Why Governance Matters: Success and Failure of Village-Owned Enterprises in Java - Teguh Yuwono (Magister Ilmu Politik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2026)
Indonesia’s decentralization has significantly transformed rural development, with the creation of Village-Owned Enterprises (BUMDes) becoming a key development strategy. However, the performance of BUMDes varies widely across regions. Most previous studies have focused mainly on economic performance, administrative arrangements, and operational accountability. These studies often overlook the socio-political factors that influence BUMDes success, such as local governance, political support, and community participation. From a governance perspective, earlier research tends to adopt a narrow approach, concentrating only on the administrative structure of BUMDes as village-owned enterprises. This approach neglects broader governance dynamics, particularly the relationships between local communities, political actors, and government institutions. This study addresses this gap by examining governance practices in both successful and unsuccessful BUMDes across four villages in Java, selected based on the Village Development Index. The findings show that successful BUMDes are typically supported by visionary and participatory leadership, strong political commitment from local governments, and active community involvement. These elements reflect a form of responsible governance and strong civic engagement. In contrast, poorly performing BUMDes tend to have passive leadership and weak political and community support, often limited to symbolic participation. Overall, the study highlights the importance of leadership, political will, and meaningful participation, and proposes an integrated governance framework that situates rural enterprises within their broader socio-political context.